An optimization-based in-motion fine alignment and positioning algorithm for underwater vehicles. (October 2022) - Jin, Kaidi; Chai, Hongzhou; Su, Chuhan; Xiang, Minzhi; Hui, Jun
Highlights: An optimization-based alignment model considering IMU bias and vehicle movement for DVL/SINS system. A positioning method utilizing the vehicle displacement in the inertial frame. Implement SQP algorithm to solve the nonlinear alignment equation. Compare the accuracy of the proposed method and tradition method with a shipborne sea trial data. Abstract: Fast and accurate in-motion alignment of strapdown inertial navigation system (SINS) is still a difficult problem in underwater missions. Conventional optimization-based alignment cannot isolate the inertial measurement unit (IMU) bias, and Kalman-based fine alignment converges slowly and requires accurately prior knowledge of the Doppler velocity logger (DVL)/SINS system. In this paper, a novel optimization-based fine alignment and positioning algorithm is proposed using DVL measurements in which the IMU bias is considered, and the geodetic coordinate of SINS is updated by the displacement in the inertial frame. In addition, the sequence secondary planning algorithm is applied to the nonlinear optimization problem. Experimental results show that the position accuracy reaches 0.36% relative to the traveled distance, and the proposed method can improve the accuracy of alignment.